Using Evaluation to Motivate Students in an Extensive Reading Program - Quinn, Kelly (Journal of ELT Research, 2018)
Extensive reading, sometimes referred to as Free Reading or Book Flood is a system of language instruction where students are encouraged to read a large volume of level appropriate material. According to Wodinsky & Nation (1998) extensive reading should focus on comprehension of the material and enjoyment. Students choose what they want to read and are not compelled to read or finish books that they find uninteresting. One of the founding principles of the original proponents of extensive reading is that the pleasure of reading “is its own reward,” Day & Bamford (1998) and so assessment should be minimized or eliminated entirely. As extensive reading has gained in popularity, this premise has been challenged. This presentation compares two reading classes, one where students read without evaluation of their comprehension and one where students, after completing the book, had to take a short quiz to test their understanding. The goal of the project was to see the effect of evaluation on the amount of reading that students did. While the best students read an equivalent or greater amount without evaluation than they did when reading with evaluation, some students read much less. The presentation will explain the background for the study, materials used and method of evaluation. Finally, it will offer some possible explanation of why certain students might require evaluation for motivation.